(untitled) (Bioscience Journal, 2015)
The elucidation of drought tolerance mechanisms in plants may facilitate the commercial exploitation of the species J. curcas in semi-arid regions. This study was designed to evaluate the growth and drought tolerance strategy of J. curcas plants grown under different water regimes. The work was carried out on an outdoor bench in full sunlight at Goiás State University, following the completely randomized experiment design with a 2x2 factorial scheme (two wild populations of J. curcas, naturally found in the states of São Paulo and Goiás, and two water supply regimes: 0% and 100% of evapotranspiration) and five replications. First a mixture of soil, sand and manure was prepared at the ratio of 3:1:0.5, respectively. The plants were irrigated daily, and at 60 days of age they were subjected to 10 days of water deficit and then rehydrated for five days. Under water deficit condition the J. curcas plants decreased the shoot growth, adjusted the leaf area to reduce the transpiration rate and increased the root system growth. J. curcas plants delay dehydration as a strategy to tolerate water deficit, for which the species reduces the transpiration rate and sustains tissue hydration using the water stored in the succulent stem.